The Effectiveness of Predict, Observe, Explain (POE) Based Modules on Learning Outcomes on Solubility and Solubility Products Materials - Hanifah Setiowati; Resi Pratiwi (Universitas Lampung, 2020)
This study aims to determine the effectiveness of using the Predict, Observe, Explain (POE) based chemistry module on student learning outcomes. The research method used was true experiment with a pretest-posttest control group design. The sample was taken by using purposive sampling technique. Data analysis was performed using SPSS 16.0 for Windows with paired sample t-test technique. The results showed that there was a significant difference in the mean learning outcomes between the experimental class and the control class. Based on the research results, it can be concluded that the chemical module based on Predict, Observe, Explain (POE) on the solubility and solubility product is effective for improving student learning outcomes.